Polyvinyl alcohol/α-zirconium phosphate nanocomposite coatings via facile one-step coassembly. (16th January 2023) - Xue, Yuanyuan; LaChance, Anna Marie; Liu, Jingjing; Farooqui, Maria; Dabaghian, Marina D.; Ding, Fuchuan; Sun, Luyi
Abstract: Polymer nanocomposites containing inorganic nanosheets have attracted high interest due to their improved stiffness and strength, enhanced barrier properties, and superior flame retardancy after properly incorporating nanosheets. α-Zirconium phosphate (Zr(HPO4 )2 ) (ZrP) is a layered compound that can be well exfoliated into single-layer nanosheets by propylamine in an aqueous dispersion. A polyvinyl alcohol (PVA)/ZrP dispersion was prepared and coated on polylactic acid (PLA) films, followed with crosslinking by glutaraldehyde (GA). The morphological, optical, thermal, barrier, and mechanical properties of the PVA/ZrP nanocomposite coatings were investigated. The ZrP nanosheets were uniformly distributed and well oriented in the PVA matrix. The coated PLA films exhibited high clarity even when containing 20 wt % of ZrP nanosheets. The crosslinked coating layer containing 20 wt % of ZrP nanosheets (PVA/ZrP-20-C) had an oxygen permeability of 0.022 [10 −16  cm 3 (STP)cm/cm 2 sPa] and water vapor permeability of 0.25 [10 −11  g (STP)cm/cm 2 s]. Compared with the neat PVA, when 20.0 wt % of ZrP nanosheets were well-aligned and properly incorporated, the Young's modulus and tensile strength of the resultant PLA nanocomposite were increased from 1.5 GPa and 29.5 MPa to 13.9 GPa and 98.3 MPa, respectively. Graphical abstract: Image 1 Highlights: Exfoliated ZrP nanosheets was incorporated into PVA via dilute solution mixing. The ZrP nanosheets were uniformly distributed and well oriented in the PVA matrix. PVA/ZrP nanocoating shows a significant reduction in OTR, significant improvement in tensile strength.